2008
DOI: 10.1111/j.1745-4530.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Fractions From Acid Hydrolysates of Almond Shells

Abstract: Acid hydrolysis of almond shells was carried out with 2.5 and 5% sulfuric acid, and the ethyl acetate soluble fraction of hydrolysates (EASH) was fractionated on a Sephadex Uppsala, Sweden) column. Three fractions were recovered from the crude extract produced by hydrolysis with 2.5% sulfuric acid (EASH-2.5), and five from the one produced with 5% sulfuric acid . The recovered fractions were assayed for phenolic content, radical-scavenging activity (measured by the a,a-diphenylb-picrylhydrazyl and Trolox eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In agreement to our work, some previous research reports indicate the use of acid/alkaline hydrolysis to recover polyphenols from different plant materials such as Brewer spent grains (Moreira, Morais, Barros, Delerue-Matos, & Guido, 2012); wheat straw (Tilay, Bule, Kishenkumar, & Annapure, 2008); hazelnut shell (Shahidi, Alasalvar, & Liyana-Pathirana, 2007); brazilnut shell (John & Shahidi, 2010); almond shell (Moure, Dominguez, & Parajo, 2008); walnut shell (Salcedo, Lopez de Mishima, & Nazareno, 2010); sunflower seed husk (De Leonardis, Macciola, & Di Domenico, 2005) and Phaseolus vulgaris seed coat (Dinelli et al, 2006).…”
Section: Acid/alkaline Hydrolysissupporting
confidence: 91%
“…In agreement to our work, some previous research reports indicate the use of acid/alkaline hydrolysis to recover polyphenols from different plant materials such as Brewer spent grains (Moreira, Morais, Barros, Delerue-Matos, & Guido, 2012); wheat straw (Tilay, Bule, Kishenkumar, & Annapure, 2008); hazelnut shell (Shahidi, Alasalvar, & Liyana-Pathirana, 2007); brazilnut shell (John & Shahidi, 2010); almond shell (Moure, Dominguez, & Parajo, 2008); walnut shell (Salcedo, Lopez de Mishima, & Nazareno, 2010); sunflower seed husk (De Leonardis, Macciola, & Di Domenico, 2005) and Phaseolus vulgaris seed coat (Dinelli et al, 2006).…”
Section: Acid/alkaline Hydrolysissupporting
confidence: 91%
“…When the overall xylose yield and phenolic content of the acid hydrolysate of wheat straw were compared with those obtained from previous studies carried out for the production of xylose (Roberto et al, 2003;Akpinar et al, 2010b) and phenolic compounds (Moure et al, 2008) from lignocellulosic materials with acid hydrolysis, it was found that the xylose yield and the phenolic contents were similar. The results showed that increase in severity of the hydrolysis conditions of wheat straw resulted with increase in phenolic yields and decrease in xylose yield.…”
mentioning
confidence: 80%
“…While hot water can extract the free phenolic acids, acid hydrolysis can release simple esterified phenolic acids. These phenolics, considered as the byproducts of acid hydrolysis of lignocellulosic materials, have potential application as food additives with antioxidant activity (Moure et al, 2008). The acid-soluble lignin fractions such as p-hydroxybenzoic acid, ferulic acid, vanillic acid, syringic acid, coumaric acid, syringaldehyde, p-hydroxybenzaldehyde and vanillin are well known.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore their total recovery seems to be justified. Some like Kudo and others [1][2][3] noticed that the peptides isolated from potato protein hydrolyzate have antioxidant properties, which are unusually profitable if used as a potential addition to food.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of potato sewage is 20-25% proteins and amino acids, 15% sugar and 20% mineral components, 14% organic acids, and other compounds such as phenolic compounds. Many researchers indicate the antioxidant properties of potato protein hydrolyzates [2][3][4][5]. Literature overview reported that waste potato proteins found application in the production of bioethanol from potato cell sap [6][7][8].…”
Section: Introductionmentioning
confidence: 99%